Introducing the Conceptual Design Process of the Armita Lunar Rover Based on ECSS - Amirhossain Adami; Zahra Pourjabari; Mohammad Azhdari; Seyed Ali Saadat dar; Haniyeh Eshaq Nia; Kazem Qolipour; Seyed Mohammad Mirmohammadi; Alireza Ahangarani Farahani (فصلنامه علوم و فناوری فضایی)
This study examines the structural design of planetary probes, introducing common configurations and methodologies. The research focuses on the system design process of the Armita lunar rover, developed for the first national probe robot competition organized by the Iran Space Research Institute. The Armita team achieved first place in the initial phase of the competition in 1401. The design process of the Armita rover adheres to the European cooperation for space standardization (ECSS) framework. Key stages of the process are briefly outlined, including the compilation and extraction of a requirements document, the development of a function-performance tree, a product tree, and the conceptual design of subsystems to meet mission objectives. According to the design results, the Armita rover has a mass of 6.9 kg and geometric dimensions of 48 × 38 × 36 cm, with a total energy consumption of 112 amp-hours. These specifications enable the rover to successfully perform its intended mission while meeting all technical, dimensional, and mass requirements.